Efficacy and safety of ultrasound-guided compared to x-ray-guided percutaneous endoscopic lumbar discectomy in China: a systematic review and pooled analysis - Zheng, Bin; Yu, Panfeng; Liang, Yan; Zhu, Zhenqi; Liu, Haiying (Frontiers in Surgery, 2025)
BackgroundPercutaneous endoscopic lumbar discectomy (PELD) has become the preferred minimally invasive surgical treatment for lumbar disc herniation. This study aims to conduct a systematic literature review and meta-analysis to assess the efficacy and safety of ultrasound-guided PELD compared to x-ray-guided PELD.MethodsA comprehensive literature search was conducted in the PubMed, Cochrane Library, Ovid:MEDLINE, Embase, and China National Knowledge Infrastructure databases up to August 2024. Studies were included if they compared ultrasound- and x-ray-guided PELD in patients with lumbar disc herniation. Risk of bias and quality of evidence were assessed using the Cochrane Collaboration tools and the Newcastle–Ottawa Scale. The meta-analysis was performed using RevMan 5.4.ResultsSeven studies were included, for a total of 767 patients (383 who underwent ultrasound-guided PELD and 384 who underwent x-ray-guided PELD). Ultrasound guidance significantly reduced fluoroscopy shots, radiation dose, fluoroscopy time, and working channel establishment time compared to x-ray guidance. Ultrasound guidance also demonstrated higher one-time puncture success rates. No significant differences were found in overall operative time, complications, postoperative pain scores (visual analog scale), or long-term functional outcomes (oxygen desaturation index and satisfaction rates).ConclusionsUltrasound-guided PELD significantly reduces radiation exposure and improves puncture efficiency compared to x-ray-guided techniques while maintaining equivalent clinical outcomes and complication rates. However, due to study limitations, including small sample sizes and geographical concentration of research, further multicenter randomized controlled trials are necessary to validate these findings across diverse populations and surgical settings.